2018
DOI: 10.1177/0310057x1804600407
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Tranexamic Acid and Lower Limb Arthroplasty—A Randomised Controlled Feasibility Study

Abstract: Tranexamic acid (TA) is widely reported to reduce bleeding and the risk of blood transfusion in patients undergoing lower limb arthroplasty. No study in this setting has had adequate power to examine for the effect of TA on either uncommon, but clinically important, adverse events or patient-centric endpoints. A large randomised controlled trial (RCT) is required to address these questions. As a preliminary feasibility study, we conducted an investigator-initiated, prospective, randomised, double blind placebo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 22 publications
0
12
0
2
Order By: Relevance
“…Finally, all three of the previous studies evaluating TXA in acetabular fracture surgery found no difference in rates of VTE [12][13][14], which is further corroborated by this cohort. TXA use has been shown to reduce transfusion rates by 8-23% in total knee arthroplasty [18][19][20][21] and by 11-28% in total hip arthroplasty [22][23][24][25]. However, a previous report in total hip arthroplasty found that TXA did not impact the extent of bone bleeding [26].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, all three of the previous studies evaluating TXA in acetabular fracture surgery found no difference in rates of VTE [12][13][14], which is further corroborated by this cohort. TXA use has been shown to reduce transfusion rates by 8-23% in total knee arthroplasty [18][19][20][21] and by 11-28% in total hip arthroplasty [22][23][24][25]. However, a previous report in total hip arthroplasty found that TXA did not impact the extent of bone bleeding [26].…”
Section: Discussionmentioning
confidence: 99%
“…The "Tranexamic Acid in Lower Limb Arthroplasty" (TALLAS) pilot trial was a feasibility study for a larger multi-centre trial to investigate the e cacy and safety of TXA in patients over 45 years of age, undergoing lower-limb arthroplasty [4]. In this double-blind randomised controlled trial, TXA was administered at a dose of 15 mg/kg and rate of 50 mg/min intravenously at skin incision (for total hip replacement) or just prior to tourniquet release (for total knee replacement) and repeated at 8 and 16 h post-operatively.…”
Section: Tallas Feasibility Study Design and Patientsmentioning
confidence: 99%
“…With the potential indications for perioperative TXA expanding there is a need for large RCTs to determine the safety and effectiveness of TXA in noncardiac surgery. 23 However, to gauge feasibility and optimise the design and value of large, pragmatic trials it is essential to first ascertain current practice and beliefs regarding perioperative TXA administration. We therefore undertook a survey of Fellows of the Australian and New Zealand College of Anaesthetists (ANZCA).…”
Section: Introductionmentioning
confidence: 99%